Politeness Strategy Used in 10th Grade Students’ Anecdote Text - Novita Mulyana; Made Budiarsa; Made Sri Satyawati (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
This research was aimed to find out the types of politeness strategy that is used by 10th grade students to express criticism towards public issues through an anecdote text as well as the implication on the teaching and learning process of anecdote text in SMK TI Bali Global Jimbaran. There were fifteen anecdote texts analyzed in this research and they were collected through a writing test conducted in a 10th grade class in SMK TI Bali Global Jimbaran. The data were classified and analyzed based on the politeness strategy theory proposed by Brown and Levinson (1987) and ethnography of communication theory proposed by Hymes (1973). The result of the analysis shows that from the fifteen anecdote texts collected, there were only two types of politeness strategy found to be used in expressing criticism, they are bald on record strategy and off record strategy. There are ten anecdote texts composed by the students found using bald on record strategy, while the other five anecdotes using off record strategy in expressing criticism towards public issues. In other words, more students still used the more risky way of expressing criticisms, therefore it is important for the teacher to choose or design a better model of learning which can improve the students’ pragmatic competence.